Does bank risk-taking behavior affect corporate income tax expenses? - Kartiko, Nafis Dwi; Firmansyah, Amrie; Mu’min, M. Silahul; Anam, Muhammad Syariful (WIM Solusi Prima, 2025)
This study examines the effect of bank risk-taking behavior on income tax expense recognized in the financial statements. The study uses a secondary data analysis approach to the annual reports and financial statements of 46 banks listed on the Indonesia Stock Exchange from 2004 to 2022, with 566 observations. The sample selection was done purposively based on certain criteria to ensure data completeness and consistency. The analysis technique used is Ordinary Least Squares (OLS) regression to identify the relationship between risk variables and tax expenses. The results show that high risk-taking behavior, as measured by SDROA and SDROE variables, negatively affects the income tax expenses reflected in the effective tax rate (ETR). Banks with high-performance volatility tend to utilize tax planning space to maintain liquidity and profitability. The difference in effect between SOE and non-SOE banks confirms that ownership structure affects flexibility in recognizing tax expenses. Pandemic conditions and reduced corporate income tax rates further strengthen the negative relationship between risk and ETR. Pandemic conditions and the reduction in corporate income tax rates during the 2020-2022 period also increase the bank's room for maneuver to manage the recognition of its tax expenses.